Genetic and morphometric differentiation between two morphs of Haematobosca sanguinolenta (Diptera: Muscidae) from Thailand - Tanasak Changbunjong; Thekhawet Weluwanarak; Sedthapong Laojun; Gerard Duvallet; Tanawat Chaiphongpachara (Current Research in Parasitology and Vector-Borne Diseases, 2024)
Haematobosca is a genus of biting fly within the subfamily Stomoxyinae of the family Muscidae. It is currently recognized to include 16 species worldwide. These species, acting as ectoparasites, are considered to have significant importance in the veterinary and medical fields. To address the color polymorphism related to the genus Haematobosca in Thailand, herein, we focused on the normal (legs mainly black) and yellow (legs mainly yellow) morphs of Haematobosca sanguinolenta and examined them for genetic differences using three molecular markers: the cytochrome c oxidase subunit 1 (cox1) and cytochrome b (cytb) genes from the mitochondrial genome as well as the internal transcribed spacer 2 (ITS2) region from the nuclear ribosomal DNA. In addition, we analyzed wing differences between the two morphs using geometric morphometrics (GM). The genetic divergences between the two morphs showed that cytb gene showed the greatest divergence, for which the average distance was 5.6%. This was followed by the combination of cox1-cytb-ITS2, exhibiting an average divergence of 4.5%, ITS2 with a divergence of 4.1%, and finally cox1, showing the lowest divergence of 3.5%. Phylogenetic analyses distinctly separated the two morphs of H. sanguinolenta; this separation was supported by high bootstrap values (97–100%). These results were further corroborated by three species delimitation methods, i.e. assemble species by automatic partitioning (ASAP), automated barcode gap discovery (ABGD), and Poisson tree processes (PTP), all of which suggested that the two morphs likely represent separate species. In addition, a GM study identified a statistically significant difference in wing shape between the two morphs of H. sanguinolenta (P < 0.05). This combination of genetic and morphometric results strongly supports the existence of two distinct species within H. sanguinolenta in Thailand.